2018
DOI: 10.1001/jamapediatrics.2018.0217
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Calculator for Estimating the Probability of Urinary Tract Infection in Young Febrile Children

Abstract: IMPORTANCE Accurately estimating the probability of urinary tract infection (UTI) in febrile preverbal children is necessary to appropriately target testing and treatment.OBJECTIVE To develop and test a calculator (UTICalc) that can first estimate the probability of UTI based on clinical variables and then update that probability based on laboratory results. DESIGN, SETTING, AND PARTICIPANTS Review of electronic medical records of febrile children aged 2 to 23 months who were brought to the emergency departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 21 publications
3
76
1
3
Order By: Relevance
“…If broad-spectrum antibiotic empirical therapy were to be considered for severe symptoms and/or potential risk factors of 3GC-resistant uropathogens, it would have implications for antimicrobial stewardship to reduce the risk of inadequate antimicrobial treatment. A predictive algorithm (UTICalc calculator) that incorporates clinical and laboratory results has been proposed to assist clinicians in identifying UTIs in febrile children younger than two years [36]. The development of a predictive model, by evaluating the risk factors for antibiotic resistance to E. coli may be useful to assist in providing empirical antibiotic therapy recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…If broad-spectrum antibiotic empirical therapy were to be considered for severe symptoms and/or potential risk factors of 3GC-resistant uropathogens, it would have implications for antimicrobial stewardship to reduce the risk of inadequate antimicrobial treatment. A predictive algorithm (UTICalc calculator) that incorporates clinical and laboratory results has been proposed to assist clinicians in identifying UTIs in febrile children younger than two years [36]. The development of a predictive model, by evaluating the risk factors for antibiotic resistance to E. coli may be useful to assist in providing empirical antibiotic therapy recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Because clinicians ultimately will need to make a dichotomous (yes versus no) decision regarding the use of antibiotics, we dichotomized the obtained probabilities using a cutoff of 5% (ie, we assumed that children with a calculated probability of UTI of $5% are diagnosed with a UTI and treated with antibiotics). The 5% treatment threshold was based on previous studies, 4,5 which found that clinicians would likely treat a child for a UTI if the probability of UTI was between 5% and 25%. We then tallied the number of children in our database with true UTI who did not receive antibiotics (hereinafter referred to as "missed") and, likewise, the number of children without UTI who were inappropriately treated with antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, hospitals should be aware of the bacteria circulating in their geographical area as well as their antibiogram; this because the first therapeutic approach to PN is necessary empiric [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%